Evaluation of plasminogen activator inhibitor-1 as a biomarker of unplanned revascularization and major adverse cardiac events in coronary angiography and percutaneous coronary intervention. Issue 191 (July 2020) - Jung, Richard G.; Simard, Trevor; Di Santo, Pietro; Dhaliwal, Shan; Sypkes, Caleb; Duchez, Anne-Claire; Moreland, Robert; Taylor, Katlyn; Parlow, Simon; Visintini, Sarah; Labinaz, Alisha; Marbach, Jeffrey; et al.
Abstract: Background: The stented coronary artery remains at high-risk of complications, particularly in the form of stent thrombosis and in-stent restenosis. Improving our ability to identify patients at high-risk for these complications may provide opportunities for intervention. PAI-1 has been implicated in the pathophysiology of stent complications in preclinical studies, suggesting it may be a clinically valuable biomarker to predict adverse events following percutaneous coronary intervention. Methods: Plasma PAI-1 levels were measured in 910 subjects immediately after coronary angiography between 2015 and 2019. The primary outcome was the incidence of unplanned revascularization (UR) at 12 months. The secondary outcome was the incidence of major adverse cardiac events (MACE). Results: UR and MACE occurred in 49 and 103 patients in 12 months. Reduced plasma PAI-1 levels were associated with UR (4386.1 pg/mL [IQR, 2778.7–6664.6], n  = 49, vs. 5247.6 pg/mL [IQR, 3414.1–7836.1], n  = 861; p  = 0.04). Tertile PAI-1 levels were predictive of UR after adjustment for known clinical risk factors associated with adverse outcomes. In post-hoc landmark analysis, UR was enhanced with low plasma PAI-1 levels for late complications (beyond 30 days). Finally, an updated systematic review and meta-analysis did not reveal an association between plasma PAI-1 and MACE. Conclusion: PAI-1 levels are not independently associated with UR nor MACE in patients undergoing angiography but associated with UR following adjustment with known clinical factors. In our landmark analysis, low PAI-1 levels were associated with UR for late stent complications. As such, future studies should focus on the mediatory role of PAI-1 in the pathogenesis of stent complications. Highlights: The stented artery remains high risk for stent failure. Plasminogen activator inhibitor-1 (PAI-1) is not associated with major adverse cardiac events. PAI-1 is associated with unplanned revascularization (UR) after adjustment. Low PAI-1 levels are associated with increased UR beyond one-month to one-year.